ANALYSIS OF STUDENTS 'ABILITY TO COMPLETE THE PROBLEM OF GEOMETRY AND BUILDING SIDE ROOMS BASED ON VAN HIELE GEOMETRY THOUGHTS ON CLASS IX STUDENTS OF SMP PGRI PONCOKUSUMO MALANG - Njurumana, Nikodemus Yiwa; Baidawi, Muhammad; Rahayuningsih, Sri (Study Program of Mathematics Education University of Muhammadiyah Malang, 2019)
The purpose of this study was to describe the ability of students' level of thinking insolving geometry problems with curved side spaces based on Van Hiele's level ofgeometry thinking in class IX students of SMP PGRI Poncokusumo Malang.This research method is descriptive qualitative research. In this case the analysis of the description of the level of thinking of students in solving geometry problems arising from the curved side space based on Van Hiele's theory. The research subjects taken were grade IX students of Poncokusumo Middle School, totaling 11 students. The instruments used were test, interview and documentation instruments.The results of the geometry problem analysis test show that the curvature shows that students have improved from previous studies where at level 0 and 1 all students have been able to achieve it, for level 2 there are 2 students who have not been able and level 3 there are 3 people who did not reach this level while for level 4 there are 5 students who are unable to achieve it. Researchers hope that the teacher who will teach the material to build curved side spaces to pay attention to methods that are suitable for students so that the student learning process does not experience complexity and pay attention to the process of working on problems and drawing conclusions. To increase the level of thinking students on geometry material, build curved side spaces can use teaching aids so that students easily understand.